Strategi Penanganan Academic Burnout Santriwati SMA Tahfidz Al-Amien Prenduan Sumenep Tahun 2024 - Ach. Nurholis Majid; Amrina Rosada (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Female students have an important role in maintaining the values ​​of Islamic education through memorizing the Qur'an. However, the density of academic activities in the Islamic boarding school environment can give rise to challenges, one of which is academic burnout, which is relevant to research in order to understand its handling strategies. Especially in Al-Amien Prenduan Tahfidz High School. This study aims to describe the pattern of academic burnout, its determinants, and handling strategies in female students of Al-Amien Prenduan Tahfidz High School. Academic burnout is an important phenomenon because female students are faced with the burden of academics and memorizing the Qur'an in the Islamic boarding school environment with teaching and learning activities. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation. Data analysis was carried out using an interactive analysis model, which includes: (1) data condensation, (2) data presentation, and (3) drawing conclusions and verification. Source and technical triangulation techniques were used to ensure the validity of the data. The results of the study show three main findings. First, the pattern of academic burnout among female students at Al-Amien Prenduan Tahfidz High School encompasses three aspects: (1) academic exhaustion, (2) loss of motivation in the educational process, and (3) inability to achieve academic goals. The two determinants of academic burnout are divided into two parts: (1) work/activity factors, such as academic load, limited control, and academic imbalance, and (2) personality factors, such as low self-confidence. The three strategies for managing academic burnout include (1) managing the study load, (2) strengthening motivation, and (3) academic and psychological mentoring programs by teachers and the principal. Academic Burnout, Determining Factors, Management Strategy